Pengaruh fraksi volume terhadap kekuatan tarik hibrid komposit serat pelepah pisang - serat kaca bermatriks epoksi - Muhammad Galih; Hilmi Iman Firmansyah (Jurnal Teknik Mesin Indonesia, 2025)
Banana leaf is a part of the banana that is rarely utilized and even used as waste by the Indonesian people. Inside the banana leaf there are fibers that can be used as a hybrid composite reinforcement material. The choice of glass fiber is because it has good strength value, light weight, and low price. This study has a goal to determine the effect of volume fraction on the tensile strength of hybrid composites of banana leaf fibers and epoxy-matrixed glass fibers. The fibers were soaked in 5% NaOH water. The volume fractions used were 40%, 50%, and 70% fiber. The specimen size standard used is ASTM D638-14 and the composite manufacturing method uses the Hand lay-up method. After conducting the tensile testing process, it was found that the 70% volume fraction had the highest tensile strength value with a stress value of 80.2 MPa and a strain value of 0.07%.